2022
DOI: 10.1111/irv.13038
|View full text |Cite
|
Sign up to set email alerts
|

Severe viral respiratory infections in the pre‐COVID era: A 5‐year experience in two pediatric intensive care units in Italy

Abstract: Background: Viral respiratory infections are one of the main causes of hospitalization in children. Even if mortality rate is low, 2% to 3% of the hospitalized children need mechanical ventilation. Risk factors for admission to the pediatric intensive care unit (PICU) are well known, while few studies have described risk factors for invasive ventilator support and prolonged hospitalization.Methods: A retrospective study including all patients aged between 2 and 18 months with a confirmed viral respiratory infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(86 reference statements)
1
2
0
Order By: Relevance
“…In a literature review of 50 articles published between October 1999 and December 2017, RSV has been outlined as the most commonly detected virus (59.2%) as well [ 24 ]. In our cohort, viral coinfection was detected in 24.1% of patients, in agreement with previous studies that describe similar coinfection rates (between 25.8% and 34.7%) [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a literature review of 50 articles published between October 1999 and December 2017, RSV has been outlined as the most commonly detected virus (59.2%) as well [ 24 ]. In our cohort, viral coinfection was detected in 24.1% of patients, in agreement with previous studies that describe similar coinfection rates (between 25.8% and 34.7%) [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The clinical significance of coinfection remains unclear. Some studies reported increased severity of coinfection, but the impact of coinfection was not particularly obvious in other studies [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being one of the commonest pediatric diseases, uncertainties remain about best diagnostics, treatment strategies and tools to recognize early risk of deterioration. In fact, one of the main challenges that pediatricians face is how to manage a child with a full-blown clinical picture of bronchiolitis but with vital parameters within normal values or borderline, since children with bronchiolitis can deteriorate within hours after initial observation [ 2 ]. While observing these children to monitor progression may be the ideal strategy, this is usually not feasible nor sustainable due to a lack of beds in the observation units and not enough healthcare resources.…”
Section: Introductionmentioning
confidence: 99%